2011
DOI: 10.1177/1754337111430569
|View full text |Cite
|
Sign up to set email alerts
|

Air flow around the point of an arrow

Abstract: The aerodynamic drag of an arrow is of importance in relation to the arrow’s drift in wind and to its down-range velocity. A significant contributor to that drag is the viscous drag from the arrow shaft, and consequently the nature of air flow over the arrow point and the location of the transition from laminar to turbulent flow are of interest. In this paper the flow was investigated using a scale model in a water channel for two arrow point profiles and for circumferential gaps at the rear of the arrow point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…Since it is highly undesirable to have the arrow shaft external diameter greater than that of the arrow point (as that would lead to carbon fibre splinters when the arrow entered the target), diameter mismatches can be expected to be a sharp reduction in diameter from the arrow point to the arrow shaft. The diameter mismatch is then likely to result in increased aerodynamic drag as shown by Park et al 3 and hence to increased wind drift as shown by Park. 2…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Since it is highly undesirable to have the arrow shaft external diameter greater than that of the arrow point (as that would lead to carbon fibre splinters when the arrow entered the target), diameter mismatches can be expected to be a sharp reduction in diameter from the arrow point to the arrow shaft. The diameter mismatch is then likely to result in increased aerodynamic drag as shown by Park et al 3 and hence to increased wind drift as shown by Park. 2…”
Section: Methodsmentioning
confidence: 89%
“…Park et al 3 considered the airflow over the arrow’s point. It was shown that for some arrow points, the flow remained laminar for the first portion of the arrow shaft, while for others, it immediately transitioned to turbulent and thus had increased aerodynamic drag.…”
Section: Introductionmentioning
confidence: 99%
“…As noted above, Park et al 12 found that with an appropriate point profile, laminar flow could be sustained up to at least an angle of attack of 3°. In each case, arrow shafts were modelled to have the same spine, maximum diameter and mass per unit length as shown for that arrow shaft in Easton Technical Products, 18 with minor modifications made to ensure consistent values for Young's Modulus and density for the carbon fibre composite material for the given arrow shaft type.…”
Section: Calculated Wind Driftmentioning
confidence: 87%
“…Careful design of the point profile can result in laminar flow along the first portion of the arrow shaft until a Reynolds number of approximately 450,000 is reached (where the characteristic length is the distance along the arrow shaft from the front of the arrow), after which the flow will be turbulent. Park et al showed that the laminar flow could be obtained up to an angle of attack of at least 3°.Figures 4-7in Park et al12 show the turbulent flow obtained with a normal point and flow transition further along the arrow shaft when an appropriately modified point profile is used. For the recurve bow and arrow noted above, transition could be expected approximately 120 mm behind the point if the modified point profile is used.…”
mentioning
confidence: 97%
See 1 more Smart Citation